MO506: Disparities in Hospitalisation Rates Between Men and Women With and Without Chronic Kidney Disease in the Irish Health System. (3rd May 2022) - Stack, Austin; Glynn, Liam; Walsh, Cathal; Shah, Silvi; Galvin, Rose; Crews, Deidra; Browne, Leonard
Abstract: BACKGROUND AND AIMS: It is increasingly recognized that disparities in health care utilisation and associated clinical outcomes exist between men and women. Whether these sex disparities extend to patients with chronic kidney disease (CKD) is not well known. The primary goal of this study was to compare hospitalisation rates between men and women in the Irish health system and study the association of kidney function with hospitalization rates. METHOD: We constructed a cohort of 125 890 patients from the National Kidney Disease Surveillance System (NKDSS) to compare hospitalization rates between men and women. Patients were recruited from 1 January 2005 to 31 December 2010 and followed until 31 December 2013. Hospitalization events were captured from the National Hospital In-Patient Enquiry (HIPE) system and linked to existing laboratory data systems. The primary cause of hospitalization was determined from the International Classification of Diseases (ICD-10), with causes grouped according to Major Diagnostic Categories (MDC). CKD was defined as an eGFR <60 mL/min/1.72 m 2 . Crude rates were calculated as the total number of hospitalizations that occurred during follow-up divided by the total number of observed person-years. Negative binomial regression determined rate ratios (RR) for men versus women with adjustment for baseline casemix. The principal exposure was participant sex, classified as men or women. RESULTS: Of the 125 890 participants, 55.1% were women, with a mean age of 54.1 (SD: 17.7) years. Compared with women, men were on average significantly older (55.1 versis 53.3 years), had higher eGFR (83.3 versus 82.4 mL/min/1.72 m 2 ), more diabetes (22.9% versus 17.0%) and higher levels of inflammatory markers (P < .001 for all). During a median follow-up of 7.7 years, there were 93 515 hospitalizations. Crude hospitalization rates (per 100 person years) were marginally higher in men than in women {11.1, [95% confidence interval (95% CI) 11.0–1.2 versus 9.8), 95% CI 9.70–9.9/100 pyr]} in the overall cohort, which changed little with adjustment for age. With each worsening category of kidney function, hospitalization rates increased substantially from 8.1 (8.0–8.3) to 28.6 (27.0–30.3) in men and from 8.1 (8.0–8.3) to 24.7 (23.5–25.9) in women, respectively. However, within each category, rates of hospitalization were significantly higher for men than for women (P-value interaction, <.001). In stratified analyses, the men-to-women risk ratios increased from 1.11 (1.02–1.21) for eGFR >90 mL/min to 1.50 (1.34–1.68) for GFR 45–59 mL/min/m² (Table 1). A similar pattern was observed when the 60 mL/min eGFR threshold was used (Table 1). The excess hospitalizations in men compared with women were in general due to higher rates of hospitalizations from circulatory disorders (5.2 versus 3.2/100 pyr), respiratory illness (4.0 versus 2.8/100 pyr), and diseases of the digestive system (2.5 versus 2.0/100 pyr), as shown in Fig. 1 . CONCLUSION: Men and women with CKD experienced hospitalization rates that were far higher than those without CKD. Hospitalization rates were greater in men than women across all stages of CKD, which was not explained by age or acute illness indicators. The excess hospitalizations in men were largely attributed to common cardio-respiratory-digestive illnesses. CKD is a major risk amplifier for hospitalization in both men and women and should be identified in all patients prior to hospitalization to ensure effective risk stratification and optimal management.